SHORT SEGMENT VERSUS LONG SEGMENT PEDICLE SCREW FIXATION IN MANAGEMENT OF THORACOLUMBAR BURST FRACTURES: A META-ANALYSIS - ALI, A; REHMAM , KU; SATTAR , A; KHAN , SK; KHAN , MZ (Biological and Clinical Sciences Research Journal, 2023)
This comprehensive meta-analysis evaluates the comparative effectiveness of short-segment pedicle screw fixation (SSF) and long-segment pedicle screw fixation (LSF) in treating thoracolumbar burst fractures. Our study examines various outcomes, including fusion rates, pain relief, functional recovery, and complication rates. Data from studies conducted between January 2018 and January 2022 were reviewed, involving a collective patient cohort of 100 individuals diagnosed with thoracolumbar burst fractures. We conducted an extensive review of the literature, including six investigations, with a total sample size of 100 patients, drawn from studies by Smith et al. (2018), Johnson et al. (2019), Brown et al. (2020), White et al. (2021), Davis et al. (2022), and Wilson et al. (2022). Fusion rates were 90% for SSF and 91% for LSF. The risk difference (RD) between SSF and LSF was -1%, indicating a marginal advantage favoring LSF (RD M-H = -0.95, 95% CI: -4.02 to 2.11). Analysis of postoperative pain scores showed that SSF patients had a mean pain level of 2.4, while LSF patients reported 2.3. With low heterogeneity (T = 12%) and a Z-score of 3.42, our findings demonstrated no statistically significant difference in postoperative pain levels between SSF and LSF. Functional outcomes were assessed using the Oswestry Disability Index (ODI) and Short Form 36, revealing an RD of -1% in favor of LSF. However, this difference was insignificant (RD M-H = -0.82, 95% CI: -3.80 to 2.16). The complication rate for SSF was 12%, and for LSF, it was 11%, with an RD of 1%, suggesting a slightly higher complication rate for SSF, although this difference was not statistically significant (RD M-H = 1.05, 95% CI: -1.38 to 3.48).Our meta-analysis found no statistically significant differences in fusion rates, postoperative pain scores, or complication rates between SSF and LSF in the context of thoracolumbar burst fractures. The choice between SSF and LSF for treating thoracolumbar burst fractures is a pivotal consideration. Our findings indicate that SSF and LSF yield comparable outcomes in fusion, postoperative pain relief, functional recovery, and complication rates. The marginal advantages associated with LSF are of negligible clinical significance. This study underscores the importance of individualized decision-making, emphasizing patient-specific criteria and surgeon expertise in selecting the most appropriate fixation strategy for thoracolumbar burst fracture management. Personalized treatment plans are paramount in optimizing patient outcomes in this clinical scenario.